The Transition from Communism: A Diagrammatic Exposition of Obstacles to the Demand for the Rule of Law - Hoff, Karla; Stiglitz, Joseph E. (World Bank, Washington, D.C., 2013)
In an earlier paper, the authors presented a mathematical exposition of a theory that demonstrated that mass privatization without institutions to limit asset-stripping may not lead to a demand for the rule of law ["After the Big Bang? Obstacles to the Emergence of the Rule of Law in Post-Communist Societies," American Economic Review 94(3), June 2004, pages 753-63]. This report makes the same argument in terms of simple diagrams. The central idea is that economic actions (to build value or strip assets) and political positions of individuals are interdependent. "Big bang" privatization may give individuals an interest in taking what they can quickly, rather than waiting for the establishment of property rights protection that would permit them to build more valuable assets. Asset stripping gives some of these individuals an interest in prolonging the absence of the rule of law so that they can enjoy the fruits of stripping without the constraint of government enforcement of property rights. Each individual, in attempting to influence society's choice of the environment, focuses on the impact on himself, not the impact on others. In choosing their economic actions, individuals ignore the effect of their economic decisions on how they themselves vote, how other people believe the system will evolve, and thus how others invest and vote. Thus, two distortions of individual behavior are associated with the public good nature of votes. The authors use this framework to make one further point. Because of the interdependence between individuals' economic and political choices, demand for and opposition to the rule of law cannot be separated from macroeconomic policy. A too stringent macroeconomic policy can lower the returns to building value relative to stripping assets and thereby weaken the equilibrium demand for the rule of law. Macroeconomic policies and institutional evolution are not independent issues.